2022
DOI: 10.1021/acs.langmuir.2c02030
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Friction and Superlubricity of Colloidal AFM Probes Coated by Tribo-Induced Graphitic Transfer Layers

Abstract: Colloidal probe atomic force microscopy (AFM) allows us to explore sliding friction phenomena in graphite contacts of nominal lateral size up to hundreds of nanometers. It is known that contact formation involves tribo-induced material transfer of graphite flakes from the graphitic substrate to the colloidal probe. In this context, sliding states with nearly vanishing friction, i.e., superlubricity, may set in. A comprehensive investigation of the transfer layer properties is mandatory to ascertain the origin … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 59 publications
1
15
0
Order By: Relevance
“…We point out that the observation of graphene patches over the beads’ surface does not ensure, by itself, the manifestation of graphene-mediated effects in contact mechanics. In fact, for the micrometric beads used in the present study (nominal diameter ∼25 μm), the circular contact spot with an ideally-smooth countersurface has a diameter of about 2 a 0 ∼300 nm (see Supplementary Figure S1 in ref for an estimate of the contact radius a 0 using a sphere-on-flat contact mechanics theory). Hence, graphene-mediated contact phenomena may appear provided that the graphene patches either exactly coat such contact spot or–which is more often the case–they prevent the silica-substrate contact by forming a new, off-centered, and topographically highest contact asperity.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…We point out that the observation of graphene patches over the beads’ surface does not ensure, by itself, the manifestation of graphene-mediated effects in contact mechanics. In fact, for the micrometric beads used in the present study (nominal diameter ∼25 μm), the circular contact spot with an ideally-smooth countersurface has a diameter of about 2 a 0 ∼300 nm (see Supplementary Figure S1 in ref for an estimate of the contact radius a 0 using a sphere-on-flat contact mechanics theory). Hence, graphene-mediated contact phenomena may appear provided that the graphene patches either exactly coat such contact spot or–which is more often the case–they prevent the silica-substrate contact by forming a new, off-centered, and topographically highest contact asperity.…”
Section: Resultsmentioning
confidence: 89%
“…This points to the promising opportunity to exploit such nanomaterials to achieve ultralow friction states and possibly superlubricity, namely, a condition in which the friction force vanishes or very nearly vanishes. It is worth mentioning that the occurrence of almost negligible friction coefficients (i.e., ≪0.01), assessing just the friction variation with the imposed normal load, does not necessarily imply vanishing values of the measured friction force and the overall absence of dissipative stick–slip regimes. , The capability to achieve superlubricity by wet-transferred graphene from a liquid dispersion still has to be demonstrated and appears of particular relevance for micro electromechanical systems (MEMS) . In fact, SLG/FLG flakes might be delivered via scalable fabrication methods (e.g., high-throughput large-area printing techniques) ,, to improve device performance (e.g., in rotating, oscillating, sliding contacts, and contact switches) or to target new mechanical functionality. , In general, for graphitic nanosystems, superlubricity develops because of the presence of atomically smooth shear planes at the contact interface.…”
Section: Introductionmentioning
confidence: 99%
“…The aim is to shed light on the relation between friction and the length parameters characterizing the contacting surfaces, i.e., the sphere diameter, D , and the LIPSS period, Λ. Colloidal spheres can be easily attached to the free end of atomic force microscopy (AFM) cantilevers. In this way, Buzio et al could observe a transition from dissipative to superlubric sliding for silica microspheres dragged on graphite and possibly contaminated by the last one . Murdoch et al demonstrated how the boundary lubrication of copolymer-coated steel microspheres sliding on a silicon wafer is enhanced by functionalizing the coating with small amounts of additives .…”
Section: Introductionmentioning
confidence: 99%
“…In this way, Buzio et al could observe a transition from dissipative to superlubric sliding for silica microspheres dragged on graphite and possibly contaminated by the last one. 4 functionalizing the coating with small amounts of additives. 5 However, these investigations focused on flat surfaces with little resemblance to those addressed here.…”
Section: Introductionmentioning
confidence: 99%
“…According to the classical friction theory, the friction pairs exhibit apparent stick–slip behavior owing to the difference (Δμ) between the static friction coefficient (μ s ) and kinetic friction coefficient (μ k ) . The Δμ, which plays a decisive role in triggering the energy of vibration, is considered to highly rely on the surface topography. The classical surface topography model demonstrates that the friction force affecting Δμ originates at the contact of the surface asperities. The contacts between asperities, such as asperity adhesion, asperity interlocking, and asperity deformation, , cause the fluctuation of the friction force, leading to stick–slip behavior. Traditionally, the contact area between asperities is estimated according to the classical Greenwood and Williamson (G–W) model .…”
Section: Introductionmentioning
confidence: 99%